2006
DOI: 10.1016/j.cellbi.2006.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and antioxidant status in blood and tissue of malignant breast tumor and benign breast disease

Abstract: Changes in the levels of malondialdehyde (MDA), nitrate and nitrite (as an index of nitric oxide production), lipid hydroperoxide (LOH), total antioxidant capacity (TAC), lipids (total cholesterol and triglycerides) and lipoproteins (HDL- and LDL-cholesterol) were estimated in breast cancer patients (n = 15) and benign breast disease (n = 15). Serum and tissue MDA levels were found to be decreased in breast cancer patients compared to the benign group (p < 0.05). In contrast, nitrate and nitrite levels were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 31 publications
9
52
0
3
Order By: Relevance
“…The higher TAO activities in our study may be due to the response of increased ROS production and excessive antioxidant consumption with inability to detoxify high levels of H 2 O 2 into H 2 O that results in the formation of the most dangerous OH -radical followed by MDA and development of oxidative stress. This finding was in agreement with Gönenc et al [47], who investigated 15 breast cancer cases and 15 controls and showed that TAO level, was elevated in the breast cancer patient group compared to control group. The apoptotic profile in our study was also investigated by estimation of circulating levels of sFas "as inhibitor of apoptosis".…”
Section: Discussionsupporting
confidence: 92%
“…The higher TAO activities in our study may be due to the response of increased ROS production and excessive antioxidant consumption with inability to detoxify high levels of H 2 O 2 into H 2 O that results in the formation of the most dangerous OH -radical followed by MDA and development of oxidative stress. This finding was in agreement with Gönenc et al [47], who investigated 15 breast cancer cases and 15 controls and showed that TAO level, was elevated in the breast cancer patient group compared to control group. The apoptotic profile in our study was also investigated by estimation of circulating levels of sFas "as inhibitor of apoptosis".…”
Section: Discussionsupporting
confidence: 92%
“…The amount of nitrite is also elevated in breast tissue from breast cancer patients (745 nmol/g wet weight) compared with the amount in benign breast disease (442 nmol/g wet weight; ref. 36). In breast tumors, the expression of NOS is associated with increased proliferation and tumor grade and the expression of PgR and nitric oxide is associated with invasive disease (37).…”
Section: Discussionmentioning
confidence: 99%
“…27 The TC and HDL values were elevated in patients with BBD as compared with breast cancer patients, but LDL and TG levels were comparable between the 2 groups. 28 Kokoglu et al 29 showed significant increases in TG and VLDL and decreases in total, HDL, and LDL cholesterol levels. In contrast, Farid et al 30 showed higher levels of cholesterol and TG in breast cancer patients.…”
Section: Discussionmentioning
confidence: 97%